2022
DOI: 10.5964/jspp.7587
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes shape implicit temporal trajectories: A quantitative test of the narrative structure of collective memories of colonialism

Abstract: This article investigates how Belgian participants’ implicit temporal trajectories regarding the history of Belgian colonialism in the Congo vary as a function of their attitudes towards colonialism and thus create different collective memories. We reasoned that, depending on their attitudes towards Belgian colonialism, individuals may draw on different schematic narrative templates to structure their own implicit temporal trajectory of colonial history. Consequently, we predicted that the shape of individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…Evidence for an implicit temporal trajectory can be indicated by a change in the degree or direction of bias in the emotional valence of cognitive representations pertaining to at least two separate temporal periods. These two periods are typically the past and the future, although some researchers have fruitfully examined implicit temporal trajectories across multiple periods in the past, for example, in Belgian representations of colonialism and decolonization of the Congo (e.g., Lastrego et al, 2022 ). The relative fluency with which people retrieve events from a target period provides a behavioral measure of cognitive accessibility (i.e., the speed or ease with which representations from a particular domain come to mind).…”
Section: Implicit Intertemporal Trajectoriesmentioning
confidence: 99%
“…Evidence for an implicit temporal trajectory can be indicated by a change in the degree or direction of bias in the emotional valence of cognitive representations pertaining to at least two separate temporal periods. These two periods are typically the past and the future, although some researchers have fruitfully examined implicit temporal trajectories across multiple periods in the past, for example, in Belgian representations of colonialism and decolonization of the Congo (e.g., Lastrego et al, 2022 ). The relative fluency with which people retrieve events from a target period provides a behavioral measure of cognitive accessibility (i.e., the speed or ease with which representations from a particular domain come to mind).…”
Section: Implicit Intertemporal Trajectoriesmentioning
confidence: 99%
“…This participant emphasized the strength and welfare of the Congolese during pre‐colonial times. As previously mentioned, we expected pre‐colonial times to be presented predominantly in positive terms to illustrate that the Congolese had a better situation before the arrival of the colonizers (Lastrego et al, 2022). Furthermore, presenting pre‐colonial times positively is expected to strengthen present collective actions as it may allow to restore a sense of agency (Makanju et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, a recent study showed that representations of the pre‐colonial situation in Congo varied according to the individual's attitude towards colonialism. If the person was anti‐colonial, then they tended to perceive pre‐colonial times as being more prosperous than colonial times (Lastrego, Janssens, Klein, & Licata, 2022). Our participants work towards decolonizing Belgium's public sphere, hence, they tended to describe pre‐colonial times in positive terms.…”
Section: Resultsmentioning
confidence: 99%
“…This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.1 As did, for instance,Lastrego et al (2022) in targeting events before, during, and after Belgian colonization of the Congo in the collective memory of younger and older Belgians.FRAMES OF COLLECTIVE TEMPORAL THOUGHT…”
mentioning
confidence: 99%
“…1As did, for instance, Lastrego et al (2022) in targeting events before, during, and after Belgian colonization of the Congo in the collective memory of younger and older Belgians.…”
mentioning
confidence: 99%